2017
DOI: 10.18632/oncotarget.17804
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation combined with allogenic natural killer cell immunotherapy improves the curative effect in patients with advanced hepatocellular cancer

Abstract: In this study, the clinical efficacy of cryosurgery combined with allogenic natural killer cell immunotherapy for advanced hepatocellular cancer was evaluated. From October 2015 to March 2017, we enrolled 61 patients who met the enrollment criteria and divided them into two groups: 1) the simple cryoablation group (Cryo group, n = 26); and 2) the cryoablation combined with allogenic natural killer cells group (Cryo-NK group, n = 35), the safety and short-term effects were evaluated firstly, then the median pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 54 publications
2
50
0
1
Order By: Relevance
“…In contrast, NK cells derived from a healthy donor (allogeneic) showed a positive response in AML patients [ 71 ], and the following studies also showed encouraging results by using haploidentical NK cells for both elderly and pediatric AML patients [ 72 74 ]. The clinical efficacy of the allogeneic NK cell adoptive immunotherapy to treat solid tumors has also been evaluated by several groups [ 75 77 ]. Lin et al had reported that percutaneous cryoablation combined with allogeneic NK adoptive transfer significantly increased the median progression-free survival of advanced HCC patients [ 75 ].…”
Section: Nk Cell-based Immunotherapy For Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, NK cells derived from a healthy donor (allogeneic) showed a positive response in AML patients [ 71 ], and the following studies also showed encouraging results by using haploidentical NK cells for both elderly and pediatric AML patients [ 72 74 ]. The clinical efficacy of the allogeneic NK cell adoptive immunotherapy to treat solid tumors has also been evaluated by several groups [ 75 77 ]. Lin et al had reported that percutaneous cryoablation combined with allogeneic NK adoptive transfer significantly increased the median progression-free survival of advanced HCC patients [ 75 ].…”
Section: Nk Cell-based Immunotherapy For Cancermentioning
confidence: 99%
“…The clinical efficacy of the allogeneic NK cell adoptive immunotherapy to treat solid tumors has also been evaluated by several groups [ 75 77 ]. Lin et al had reported that percutaneous cryoablation combined with allogeneic NK adoptive transfer significantly increased the median progression-free survival of advanced HCC patients [ 75 ]. And multiple allogeneic NK cell infusion was associated with better prognosis in advanced cancers, including advanced HCC [ 75 ] and stage III pancreatic cancer [ 76 ].…”
Section: Nk Cell-based Immunotherapy For Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging clinical efficacy has been observed in trials of acute myeloid leukemia [110] . Moreover, cryoablation combined with allogeneic NK cell therapy markedly improved the progression-free survival of patients with advanced HCC [111] . Besides autologous and allogeneic NK cells, NK-92 cells, an NK cell line, is also used in clinical trials of cancer therapy, with encouraging results observed in patients with advanced lung cancer [112] .…”
Section: Nk Cell Therapymentioning
confidence: 99%
“…50 This is of particular importance because tumor cells can downregulate surface MHC I expression as an immune escape mechanism to evade tumor-specific T cells. 51 Activated NK cells can also interact with DCs to improve DC tumor antigen uptake and presentation. 50 Furthermore, activated NK cells can produce proinflammatory cytokines (including interferon-g), which shift CD4-positive T cells toward T helper 1 cell-mediated immune responses and stimulate CD8-positive T cells to become CTLs, which are capable of destroying tumor cells.…”
Section: Cryoimmunotherapy Combined With Nk Cell Immunotherapymentioning
confidence: 99%